2020
DOI: 10.1021/acsnano.0c03239
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanoassemblies of Cyclic Polymers Show Amplified Responsiveness and Enhanced Protein-Binding Ability

Abstract: The physicochemical properties of cyclic polymer adsorbates are significantly influenced by the steric and conformational constraints introduced during their cyclization. These translate into a marked difference in interfacial properties between cyclic polymers and their linear counterparts when they are grafted onto surfaces yielding nanoassemblies or polymer brushes. This difference is particularly clear in the case of cyclic polymer brushes that are designed to chemically interact with the surrounding envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 77 publications
2
26
0
Order By: Relevance
“…In particular, at relatively low C 0 (5 wt%) C ‐PEOXA showed significantly higher GF with respect to L ‐PEOXA ( p < 0.001), which could be attributed to the inherently different conformation of linear and cyclic polymer precursors in solutions. The steric constraints within cyclic PEOXA precursors in solution presumably lead to an enhanced exposure of functional side chains, [ 49 ] and thus to an augmented accessibility of cross‐linkable moieties (SH and VS) with respect to that characteristic of their linear counterparts. This phenomenon could determine a more efficient cross‐linking reaction and incorporation of cyclic PEOXA precursors within the network, eventually providing higher values of GF, especially at relatively low polymer contents ( C 0 ≤ 10 wt%).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, at relatively low C 0 (5 wt%) C ‐PEOXA showed significantly higher GF with respect to L ‐PEOXA ( p < 0.001), which could be attributed to the inherently different conformation of linear and cyclic polymer precursors in solutions. The steric constraints within cyclic PEOXA precursors in solution presumably lead to an enhanced exposure of functional side chains, [ 49 ] and thus to an augmented accessibility of cross‐linkable moieties (SH and VS) with respect to that characteristic of their linear counterparts. This phenomenon could determine a more efficient cross‐linking reaction and incorporation of cyclic PEOXA precursors within the network, eventually providing higher values of GF, especially at relatively low polymer contents ( C 0 ≤ 10 wt%).…”
Section: Methodsmentioning
confidence: 99%
“…9 Still, the rich information contained in combined Δf n and ΔD n measurements, especially when complemented with theoretical models representing the response for viscoelastic films, 10−12 has turned out to be very valuable in multiple research areas, including hydration analysis of organic polymers, 13,14 proteins, 15 and biological membranes. 15,16 QCM has also been widely applied to monitor and characterize thin films, including porosity determination, 17,18 monitoring the growth of mesoporous materials, 19 probing responsiveness of polymeric coatings, 20 and characterization of biomimetic membranes. 21,22 Additionally, QCM has been extensively employed to study discrete adsorbates such as abiotic and biological macromolecules and nanoparticles (NPs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Still, the rich information contained in combined Δ f n and Δ D n measurements, especially when complemented with theoretical models representing the response for viscoelastic films, has turned out to be very valuable in multiple research areas, including hydration analysis of organic polymers, , proteins, and biological membranes. , QCM has also been widely applied to monitor and characterize thin films, including porosity determination, , monitoring the growth of mesoporous materials, probing responsiveness of polymeric coatings, and characterization of biomimetic membranes. , Additionally, QCM has been extensively employed to study discrete adsorbates such as abiotic and biological macromolecules and nanoparticles (NPs). These studies included investigations of biomolecular interactions of proteins , and viruses; , structure, , confirmation , and orientation changes of biomacromolecules; spatial distribution, size, deformation , and dissolution of NPs; protein corona formation on amyloids; interactions between NPs and biomimetic membranes; , as well as bioanalytical sensor development. …”
Section: Introductionmentioning
confidence: 99%
“…26 On surfaces, a very recent report from our group suggested that the intramolecular steric constraints characterizing cyclic, weak polyacid brushes lead to a broadening in their pHresponsiveness. 27 Despite this initial study, a comprehensive understanding about the effect of PE-brush topology on its pH-responsive properties has not been achieved yet, and to what extent pHinduced swelling can be tuned through the combined modulation of polymer topology and composition has not been determined.…”
mentioning
confidence: 99%